Peran Strategis Need Assessment dalam Perencanaan Program Bimbingan dan Konseling Komprehensif : Tinjauan Literatur - Suci Amelia Mardiah; Zadrian Ardi; Nurfarhanah Nurfarhanah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This paper aims to examine the importance of needs assessment in planning Guidance and Counseling programs in educational units. Based on a literature review of various empirical articles and reviews, it is known that needs assessment is the main foundation in designing effective, contextual, and responsive guidance services to students' needs at the private, social, academic, and career levels. This study method uses a systematic literature review approach and content analysis of 10 academic articles from national and international journals. The results show that the success of the BK program is highly dependent on the implementation of accurate and integrative assessments, especially in the digital era and multicultural society. The conclusion of this study recommends strengthening the capacity of BK teachers in conducting assessments based on data and digital technology.